The Pillars and Conditions of the Marriage Contract under the Jordanian Personal Status Law No. (15) of 2019: An Analytical and Jurisprudential Study - Rasha Mohammed Khalif Al-Marafi, (International Journal of Law Research and Studies, 2026)
This study examines an analytical approach to the pillars and conditions of the marriage contract in contemporary Jordanian legislation, with particular emphasis on the amendments introduced by the Jordanian Personal Status Law No. (15) of 2019. The research aims to clarify the legal provisions governing the formation, validity, effectiveness, and binding nature of the marriage contract, while comparing them with the jurisprudential rules upon which the Jordanian legislator relied. The study concludes that the Jordanian law has regulated the marriage contract in a manner that takes into account the objectives of Islamic Sharia and achieves both familial and societal interests, while introducing certain amendments aimed at protecting the rights of the parties involved, particularly women and minors.
Keywords: Marriage Contract; Jordanian Personal Status Law; Pillars of Marriage; Conditions of Marriage; Void Marriage; Irregular Marriage